2008
DOI: 10.1111/j.1365-2761.2008.00902.x
|View full text |Cite
|
Sign up to set email alerts
|

Chemotaxis towards, adhesion to, and growth in carp gut mucus of two Aeromonas hydrophila strains with different pathogenicity for common carp, Cyprinus carpio L.

Abstract: Characteristics that promote bacterial colonization of the intestinal mucosal surface were examined in two strains of the common fish pathogen Aeromonas hydrophila, with different pathogenicity. The characteristics examined were chemotactic activity towards mucus, bacterial adherence to mucus and growth in mucus. Intestinal gut mucus of healthy common carp was used. The results indicate that chemotaxis is not necessary for a bacterium to become pathogenic, but it may be a necessary parameter for a bacterium to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
37
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(40 citation statements)
references
References 47 publications
(67 reference statements)
3
37
0
Order By: Relevance
“…After adhesion of bacteria to mucus, further steps are necessary to cause an infection. A. hydrophila 38 grew better than A. hydrophila 60 in mucus-supplemented media (Van der Marel et al 2008). Also in the present study, the cytotoxicity of A. hydrophila 38 was higher than those of the 2 other A. hydrophila strains.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…After adhesion of bacteria to mucus, further steps are necessary to cause an infection. A. hydrophila 38 grew better than A. hydrophila 60 in mucus-supplemented media (Van der Marel et al 2008). Also in the present study, the cytotoxicity of A. hydrophila 38 was higher than those of the 2 other A. hydrophila strains.…”
Section: Discussionsupporting
confidence: 51%
“…Binding of mucus to the plate was confirmed by a lectin binding assay using ConA as described previously (Neuhaus et al 2007b). Bacterial adhesion to mucus was assessed as described previously (Van der Marel et al 2008). In brief, fluorescently labelled bacteria (25 µl of 10 9 CFU ml -1 ) were added in triplicate to plates coated with mucus.…”
Section: Animalsmentioning
confidence: 99%
“…Furthermore, mucins bind a range of bacteria and constitute an important part of the mucosal defense against infection (20). However, it has also been suggested that binding to mucins could provide the pathogen with an adhesion site and thereby instead promote infection (22), although no conclusive evidence for this exists. The mucous niche is very unstable, and pathogen binding to mucins may instead serve as a decoy for the more intimate adherence that can occur between the pathogen and, e.g., glycolipids of the cell membrane.…”
mentioning
confidence: 98%
“…However, the fish often develop hemorrhagic septicemia caused by the Gram-negative bacterium, Aeromonas hydrophila, which is a part of the environment flora and becomes infectious during stress (van der Marel et al 2008). Therefore, expression of Hsp genes during A. hydrophila served a dual response to infection and stress.…”
Section: Introductionmentioning
confidence: 99%